Control of a stand-alone photovoltaic/battery bank system to supply energy to resistance load - G. Giftson Samuel; M. Muthuramaligam; P. S. Manoharan; C. Christober Asir Rajan (Institute of Advanced Engineering and Science, 2019)
In this paper, supervisor control for stand-alone hybrid power system to supply energy to resistance load is presented. The hybrid system is used to produce energy withoutinterruption and it consists of a photovoltaic generator (PV), and a battery bank. PV system work in parallel via DC/DC converter and the battery bank is used to store the excess of energy. The mathematical model topology, the identification of each subsystem and the control supervision of theglobal system are the contribution of this paper. Obtained results under Matlab/Simulink presented and discussed.